KALIMAT IMPERATIF BAHASA MASSENREMPULU (ImperativeSentence of Massenrempulu Language) - Syamsul Rijal (Balai Bahasa Sulawesi Selatan, 2014)
The research aims at describing imperative sentence in Massenrempulu language. Method used isdescriptive with noting and recording technique. In addition, documentation analysis of previous study aboutMassenrempulu language and literature is also done. Data analysis applies structural linguistic theory. Result of research shows that imperative sentence of Massenrempulu language has falling intonation at the end of sentence, its pattern is [2]3 2 //[2]1#. Based on its type, imperative sentence of Massenrempulu language isdivided into seven groups, they are intransitive imperative sentence, transitive imperative sentence, requestingimperative sentence, prohibitive imperative sentence, permission imperative sentence, indirect imperativesentence, and offering imperative sentence.